Sejarah perkembangan undang-undang keselamatan pekerjaan di Amerika Syarikat dan United Kingdom, serta pengaruhnya terhadap Malaysia - Md Ismail, Che Thalbi (Dewan Bahasa dan Pustaka, 2016)
This article begins the discussion by explaining the historical development of the occupational safety law of the United Kingdom and the United States of America. Further, the discussion is widened to examine the influence of the said countries on the development of Malaysian law. In Malaysia, the development of occupational safety law started with the introduction of the Factory and Machinery Act 1967 and its regulations. Such legislation is considered to have been a good start in the development of occupational safety law. Next, the Occupational Safety and Health Act 1994 was drafted and this complemented the laws by governing almost all industries and also imposing the liability of ensuring workers’ safety and health not only on employers, but also various other parties. The historical analysis method is adopted here to examine whether the law in these western countries was duplicated in their entirety in Malaysia or whether it has gone through some modification process to suit the local application. It is also worthy to note that analysis of the development of the Common Law principles is also included since its application in Malaysia was approved via the Civil Law Act 1956.